Síntese de 1,2,4-triazol-5-ilamino pirimidinas trifluormetil substituídas - Bortolotto, Guilherme Pivotto (2009)
This work describes the synthesis and characterization of fourteen 4-trifluoromethyl-2-[3-(pyridyl)-1H-1,2,4-triazol-5-ylamino]pyrimidines (6, 7), from the cyclocondensation reaction of N-[3-(pyridyl)-1H-1,2,4-triazol-5-yl]guanidines (4, 5), a 1,3-dinucleophile precursor of the type (N-C-N), with 1,1,1-trifluoro-4-alkoxy-3-alken-2-ones (1), a versatile 1,3-dieletrophile. The 1,1,1-trifluoro-4-alkoxy-3-alken-2-ones (1), of the general formula F3C-C(O)- CH=C(R)-OR1 where R1 = Me, Et and R = H, Me, Ph, 4-FPh, 4-MePh, 4-OMePh, Furyl, were obtained from trifluoroacetylation reactions of enolethers or acetals derived of acyclic ketones. The reactions of 1,1,1-trifluoro-4-alkoxy-3-alken-2-ones (1) with N-[3-(pyridyl)-1H-1,2,4-triazol-5-yl]guanidines (4, 5) was carried in ethanol in reflux for 18 hours, leading to end products in 40-68% yield. The compounds were characterized by 1H and 13C NMR experiments, and the purity these compounds proved by elemental analysis.